The Effect of Government Expenditures in Agriculture on Gross Regional Domestic Products of the Agricultural Sector in Lampung Province - Prapti Lestari; Toto Gunarto; Neli Aida (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Agricultural sector is the dominant sector in Lampung Province with a contribution of 29.90 percent to the Gross Regional Domestic Product (GRDP) of Lampung Province. The majority of Lampung residents also work in the agricultural sector. As the base sector, the government continues to support this sektor. The government's budget for the agricultural sektor through local government budget, Physical Specific Allocation Fund, and the Kredit Usaha Rakyat (KUR) policy continues to increase during 2017-2020. However, the GRDP growth of the agricultural sector in Lampung Province continues to decline. This study aims to analyze the effect of local Government Budget, Physical Specific Allocation Fund, KUR, and labor in the agricultural sector on the GRDP of the agricultural sektor in Lampung Province. This study use secondary data 15 district/city in Lampung Province. By using panel data regression, the results show that the local government budget and KUR in the agricultural sector have a significant and positive effect, while the physical Specific Allocation Fund in the agricultural sector actually has a negatif effect on the GRDP of the agricultural sector. The local government needs to continue optimizing the local government budget and expand the distribution of KUR as support to promote growth of the agricultural sector in Lampung.